2020
DOI: 10.1111/echo.14861
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between mitral annular calcification and cardiovascular events: A meta‐analysis

Abstract: Background Mitral annular calcification (MAC) is prevalent in the aging population, with recent renewed interest regarding its associations with cardiovascular risk factors, outcomes, and influence on valvular heart disease and interventions. This meta‐analysis aimed to report the relationships between MAC and cardiovascular mortality and morbidity events. Methods Relevant studies were searched from PubMed, Cochrane, and Embase databases until November 30, 2019. Associations between MAC as a binary variable wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 52 publications
(113 reference statements)
0
8
0
Order By: Relevance
“…Therefore, we focused on the association between progressive calcification and left valvular disease. Several meta-analyses have indicated an association between AVC and MVC and worse outcomes in the general population with or without CVD 27 30 . While AVC and MVC share similar contributing factors, such as aging, abnormal calcium and phosphate metabolism, and systemic atherosclerosis 31 , previous studies have reported differences in the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we focused on the association between progressive calcification and left valvular disease. Several meta-analyses have indicated an association between AVC and MVC and worse outcomes in the general population with or without CVD 27 30 . While AVC and MVC share similar contributing factors, such as aging, abnormal calcium and phosphate metabolism, and systemic atherosclerosis 31 , previous studies have reported differences in the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with a recent meta‐analysis where the presence MAC was an independent predictor of mortality and major adverse cardiovascular events. 22 …”
Section: Discussionmentioning
confidence: 99%
“…58 Although not as well studied as CAVD, the clinical associations between increased mitral annular calcification and worsening cardiovascular morbidity and mortality are evident. 59 In a study of 204 CKD patients stages 2 and 3, >30% of the study participants had detectable aortic or mitral valve calcification, 60 and other studies have observed even higher rates of aortic valve abnormalities. 20 Declining renal function accelerates mineral deposition in these tissues, with severe valvular dysfunction observed in patients significantly younger than the general population.…”
Section: Calcification Of the Cardiac Valvesmentioning
confidence: 95%
“… 58 Although not as well studied as CAVD, the clinical associations between increased mitral annular calcification and worsening cardiovascular morbidity and mortality are evident. 59 …”
Section: Heterogeneity Of Cardiovascular Calcification and Its Clinic...mentioning
confidence: 99%